DEVELOPMENT OF A TRAINING COURSE TO ENHANCE COMPETENCY-BASED INSTRUCTION FOR TEACHERS AND FOSTER STUDENTS’ PROBLEM-SOLVING ABILITIES AT SMALL PRIMARY SCHOOLS USING THE GF-TOR MODEL - Surayothin, Junlamanee; Nakin, Sirirat; Thongpakdee, Lalita (Journal of Education and Innovation, 2025)
Through a research and development process, this study aimed to: 1) identify key information for a training course to enhance competency-based instruction for teachers, 2) develop the course curriculum, 3) trial it, and 4) evaluate its effectiveness. The sample group for the trial comprised 44 participants, including teachers from small-sized schools under the Nakhon Ratchasima Primary Educational Service Area Office 2-4 and upper primary school students from 10 schools. The research tools included the course curriculum and manual, a competency-based instruction knowledge test, an evaluation of active learning activity design, teacher competency assessment, problem-solving skills test, and a satisfaction questionnaire. Statistical analyses involved mean, percentage, standard deviation, and t-tests. The research findings revealed significant insights: 1) The overall competency of teachers in competency-based instruction was found to be at a moderate level, with a notable proficiency in implementing it within the classroom setting. 2) The curriculum encompassed eight critical elements: background and importance, principles, aims, structural units (competency-based instruction, design and application of learning innovations, development of plans for active learning activities, and teaching practices), content (competency-based instruction and proactive activities), systematic training using change creation processes, learning media/resources, and competency-based evaluation, all expertly assessed for quality. 3) The trial results of the curriculum revealed: (1) Teachers demonstrated increased knowledge post-training, surpassing the 70% criteria with statistical significance at the .05 level. (2) Teachers exhibited a high level of ability in designing active learning activities. (3) Teachers showed high level of competency in organizing competency-based instruction. (4) Teachers expressed high level of satisfaction with the training and curriculum utilization. Subsequent testing indicated significant improvement in students’ problem-solving skills post-class, surpassing the .05 significance level, with an 80% increase exceeding the criteria. 4) The course evaluation met criteria for context, inputs, processes, and outputs, indicating high quality and suitability for further use and dissemination.